Accounting Treatment of Coffee as Bearer Plant Asset at Perumda Perkebunan Kahyangan Jember - Suteja, Diana; Febriana Suryawati, Rindah; Soetedjo, Soegeng; Yuniarti, Anny; Sauri, Sofyan; Puspitasari, Leny (Jurnal Manajemen dan Organisasi, 2024)
This study explores the accounting treatment of coffee plant as a bearer plant asset at Perumda Perkebunan Kahyangan Jember, a local state-owned enterprise in East Java Province Indonesia. As the agricultural sector plays a crucial role in Indonesia's economy, the proper classification, recognition, measurement, and disclosures of coffee plant as bearer plants are critical for financial transparency and effective management. This study examines how relevant Indonesian Financial Accounting Standards (i.e. PSAK 16 Revision 2011 on Fixed Assets, PSAK 69 on Agriculture, PSAK 14 on Inventory, and PSAK 48 on Impairment of Assets) and International Financial Reporting Standard (i.e. IAS 41) applied in the financial reporting of coffee as a bearer plant at Perumda Perkebunan Kahyangan Jember. Using a qualitative research method with the case study approach, this study provides empirical evidence on how the implementation of such accounting standards, and the obstacle faced by the company presented based on the perspective of recognition, measurement, and disclosure relevant to coffee plant.